PENGARUH SURAT TEGURAN TERHADAP PENCAIRAN TUNGGAKAN PAJAK DENGAN SURAT PAKSA SEBAGAI VARIABEL INTERVENING (Studi Pada Kantor Pelayanan Pajak Pratama Malang Utara) - Susilo, Heru; Agusti, Rosalita Rachma; Fatmadika, Dina (Jurnal Mahasiswa Perpajakan, 2016)
The research to explain determine of exhortation letter on the liquefaction of lease arrears with letter force as intervening variable of Tax Office North Malang. Research type is explanatory research with quantitative approach. The population used time series with saturated sampling method. Source of data is collected from the secondary data. Analysis used is descriptive analysis and inferential analysis. The variable exhortation letter significantly on variable letter force ofÂ  coefficients 0,353 beta and value of sig 0,006 (0,006<0,05). Variable exhortation letter against the liquefaction of lease arrears significantly 0,467 and value of sig 0,000 (0,000<0,05), variable letter force on the liquefaction of lease arrears also affected as much as 0,354 and value of sig 0,001 (0,001<0,05), and letter force as intervening variable also affected as much as 0,124. Inferential that exhortation letter influencing letter force and liquefaction of lease arrears, either through direct or also indirectly. Key Words: Exhortation Letter, Letter Force, Liquefaction of lease arrears ABSTRAK Penelitian digunakan menguji pengaruh surat teguran terhadap pencairan tunggakan pajak dengan surat paksa sebagai variabel intervening pada KPP Pratama Malang Utara. Penelitian penjelasan dengan pendekatan kuantitatif merupakan jenis penelitian yang digunakan. Populasi yang digunakan data runtutan waktu dengan metode sampling jenuh. Sumber data dari data sekunder. Terdapat analisis deskriptif dan analisis inferensial. Variabel surat teguran berpengaruh terhadap variabel surat paksa dibuktikan nilai koefisien beta 0,353 dan nilai sig (0,006<0,05). Variabel surat teguran terhadap variabel pencairan tunggakan pajak 0,467 dan sebesar (0,000<0,05), surat paksa terhadap variabel pencairan tunggakan pajak juga 0,354 dan nilai probabilitas (0,001<0,05), dan untuk surat paksa sebagai variabel intervening berpengaruh 0,124. Kesimpulannya bahwa surat teguran mempengaruhi surat paksa dan pencairan tunggakan pajak, baik secara langsung maupun secara tidak langsung. Kata Kunci: Surat Teguran, Surat Paksa, Pencairan Tunggakan Pajak